2020
DOI: 10.1021/acsaem.0c00238
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ionic Transport and Structural Stability of Nb-Doped O3-NaFe0.55Mn0.45–xNbxO2 Cathode Material for Long-Lasting Sodium-Ion Batteries

Abstract: Sodium-ion batteries (SIBs) are promising candidates for inexpensive and sustainable energy storage devices for the widespread utilization of intermittent renewable energy because of the natural abundance of sodium raw materials. However, since the ionic radius of Na + is inherently larger than that of Li + , Na-based intercalation materials often suffer from poor stability and slow reaction kinetics. Regarding SIB cathodes, layered transition metals oxides (Na x TMO 2 ) show promising theoretical capacities b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Other elements such as Mg, Al, and Nb have also been explored as dopants to overcome the capacity fading issues of FeÀ Mn binary cathodes. [135][136][137][138][139] Al-doping could slightly increase the electrical conductivity and Na-ion diffusivity of O3-type NaFe 0.5 Mn 0.5 O 2 . However, negligible improvements on the kinetics and stabilities of the electrochemical reaction were observed.…”
Section: Other Ternary Oxidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Other elements such as Mg, Al, and Nb have also been explored as dopants to overcome the capacity fading issues of FeÀ Mn binary cathodes. [135][136][137][138][139] Al-doping could slightly increase the electrical conductivity and Na-ion diffusivity of O3-type NaFe 0.5 Mn 0.5 O 2 . However, negligible improvements on the kinetics and stabilities of the electrochemical reaction were observed.…”
Section: Other Ternary Oxidesmentioning
confidence: 98%
“…[135] By contrast, Nb-doping in O3-type NaFe 0.55 Mn 0.45 O 2 obviously enhances both the rate capabilities and cycling stabilities of the parent material owing to larger lattice spacing, better reversibility of O3-P3 phase transition, and higher material conductivity. [137] For P2-type Na 2/3 Fe 1/2 Mn 1/ 2 O 2 , it is reported that Al-substitution for Mn or Fe could promote Na + diffusion and strengthen structural stability by manipulating lattice spacing and TMÀ O/OÀ O bonding, resulting in improved rate and cycling performances, particularly in the case of Al substituting for Fe. [136] Zhou et al obtained a P2/O3 bi-phase Na 0.67 Fe 0.425 Mn 0.425 Mg 0.15 O 2 by using Mg substitution, demonstrating enhanced capacity retention in comparison with Na 2/3 Fe 1/2 Mn 1/2 O 2 .…”
Section: Other Ternary Oxidesmentioning
confidence: 99%
“…Moreover, improved conductivity was observed and attributed to the partially reduced valence of TM ions. [ 77 ] Ma et al [ 78 ] reported that Sb 5+ (radius: 0.6 Å) in the TM layer promotes the formation of a honeycomb‐ordered cathode, which shows an unusually high voltage due to Coulombic repulsions with the Sb 5+ ions in the honeycomb lattice. Similarly, the Sn 4+ (radius: 0.69 Å) doping in the TM layer increases the working voltage.…”
Section: Modulation Technologiesmentioning
confidence: 99%
“…Therefore, choosing appropriate transition metals to form binary or multicomponent layered transition metal oxides is a trend for the commercialization of layered transition metal oxide materials. At present, a variety of binary‐layered transition metal oxide cathodes have been reported in the literatures, such as Ni/Mn based, 77–79 Co/Mn based, 80 Fe/Mn based, 81 Ti/Ni based, 82 and so forth. Figure 6 shows the discharge curves of common binary‐layered metal oxides 83 …”
Section: Binary‐layered Metal Oxidesmentioning
confidence: 99%
“…However, this material contained obvious voltage delay at 3.0–4.2 V, which may be caused by the migration of Fe ions. Common solution for this problem is to introduce Li, 107 Ti, 108 Nb, 81 and other elements into the Na x [FeMn]O 2 structure to inhibit Fe‐ion migration. In addition, designing mixed phase is another good way to stabilize the lattice structure of Fe/Mn‐based transition metal oxides.…”
Section: Binary‐layered Metal Oxidesmentioning
confidence: 99%